2017
DOI: 10.1103/physrevb.96.174107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe and Co substitution on the martensitic stability and the elastic, electronic, and magnetic properties ofMn2NiGa: Insights fromab initiocalculations

Abstract: We investigate the effects of Fe and Co substitutions on the phase stability of the martensitic phase, mechanical, electronic and magnetic properties of magnetic shape memory system Mn2NiGa by first-principles Density functional theory(DFT) calculations. The evolution of these aspects upon substitution of Fe and Co at different crystallographic sites are investigated by computing the electronic structure, mechanical properties (tetragonal shear constant, Pugh ratio and Cauchy pressure) and magnetic exchange pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…The configurational ordering of the constituent elements in the crystal lattice affects both the martensitic transformation characteristics and the magnetic properties of Ni-Mn-based alloys 42,49,59,60 . First-principles calculations [61][62][63] demonstrated that the substituent 3dtransition metals do not always prefer to occupy the sites of substitutions. Therefore, we first focus on determination of the site preferences and the associated magnetic ground states of the substituted Ni 2 Mn 1.5 Sb 0.5 compounds in their high temperature austenite phases, by comparing total energies of various possible site ordered and magnetic configurations at fixed compositions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configurational ordering of the constituent elements in the crystal lattice affects both the martensitic transformation characteristics and the magnetic properties of Ni-Mn-based alloys 42,49,59,60 . First-principles calculations [61][62][63] demonstrated that the substituent 3dtransition metals do not always prefer to occupy the sites of substitutions. Therefore, we first focus on determination of the site preferences and the associated magnetic ground states of the substituted Ni 2 Mn 1.5 Sb 0.5 compounds in their high temperature austenite phases, by comparing total energies of various possible site ordered and magnetic configurations at fixed compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Quaternary off-stoichiometric Ni-Mn based Heusler compounds are found to exhibit better mechanical properties such as ductility, corrosion resistance, machinability, all of which ease manufacturing and increase the product longevity. For example, Fe-addition improves the toughness of Ni-Mn-Ga allloys without sacrificing its magnetic and thermoelastic properties 25,62 . In this section, we, therefore, explore the changes in the mechanical properties of Ni 2 Mn 1.5 Sb 0.5 compounds upon substitution by the fourth element.…”
Section: E Mechanical Propertiesmentioning
confidence: 99%
“…Since, site occupancies in the compounds do not always follow a regular pattern (the excess atoms occupying the sites of deficient atoms in the reference system) 52,[59][60][61][62][63] affecting the MCE properties as a consequence, we first found out the minimum energy configuration for each composition by comparing the total energies of configurations with different site occupancy patterns and magnetic configurations. We found that the substituting Fe/Co atoms prefer to occupy the Ni sites, whereas the Cu atoms prefer to occupy the Sb sites, the same as found out in Ref 29.…”
Section: Resultsmentioning
confidence: 99%
“…These exchange parameters were then used for the calculation of T c . The Curie temperatures were estimated with two different approaches: the mean-field approximation (MFA) 48,49 and the Monte Carlo simulation (MCS) method [50][51][52] . Details of the calculations using these methods are given in the supplementary material.…”
Section: A First-principles Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation